Change of direction speed: Toward a strength training approach with accentuated eccentric muscle actions - Chaabene, H.; Prieske, O.; Negra, Y.; Granacher, U. (Sports Medicine, 2018)
There is growing evidence that eccentric strength training appears to have benefits over traditional strength training (i.e., strength training with combined concentric and eccentric muscle actions) from muscular, neuromuscular, tendinous, and metabolic perspectives. Eccentric muscle strength is particularly needed to decelerate and stabilize the body during the braking phase of a jump exercise or during rapid changes of direction (CoD) tasks. However, surprisingly little research has been conducted to elucidate the effects of eccentric strength training or strength training with accentuated eccentric muscle actions on CoD speed performance. In this current opinion article, we present findings from cross-sectional studies on the relationship between measures of eccentric muscle strength and CoD speed performance. In addition, we summarize the few available studies on the effects of strength training with accentuated eccentric muscle actions on CoD speed performance in athletic populations. Finally, we propose strength training with accentuated eccentric muscle actions as a promising element in strength and conditioning programs of sports with high CoD speed demands. Our findings from five cross-sectional studies revealed statistically significant moderate- to large-sized correlations (r=0.45-0.89) between measures of eccentric muscle strength and CoD speed performance in athletic populations. The identified three intervention studies were of limited methodological quality and reported small- to large-sized effects (d=0.46-1.31) of strength training with accentuated eccentric muscle actions on CoD speed performance in athletes. With reference to the available but preliminary literature and from a performance-related point of view, we recommend strength and conditioning coaches to include strength training with accentuated eccentric muscle actions in training routines of sports with high CoD speed demands (e.g., soccer, handball, basketball, hockey) to enhance sport-specific performance. Future comparative studies are needed to deepen our knowledge of the effects of strength training with accentuated eccentric muscle actions on CoD speed performance in athletes.